Evolving Habitus and Gender Identity: A Bourdieusian Analysis of Bina Shah’s Nonfiction Narratives - Rashid, Faiqa; Anwar, Nadia (Journal of Research in Humanities, 2023)
This research paper unfolds the agency of women developed by and experienced in patriarchal Pakistani society as depicted in Bina Shah’s nonfiction narratives. Shah offers a counternarrative to the EuroAmerican portrayal of Pakistani women by debunking the stereotypical narratives about their suppression and exploitation. Pierre Bourdieu’s ‘Cultural Field’ (1993) and Glynis Breakwell’s Identity Process (1986) theories have been used to understand what habitus women manifest in the ‘cultural field’ and how it evolves in Shah’s nonfiction narratives that underscore women’s nontraditional ‘positions and identity development in the same field. This research also attempts to evaluate the identity threats posed to women when they are deprived of ‘symbolic capital’ in a patriarchal society. Thematic analysis of Shah’s articles published in Dawn and posted on her blog Bina Shah, Feministani will be done to elucidate the identity formation of Pakistani women. This interdisciplinary research which embraces the domains of literature, journalism, sociology, and gender studies will also clarify the significant role of literary writers in re/shaping perceptions of gender identity prevalent in Pakistani society.